Additive manufacturing - Bandyopadhyay, Amit, 1967-; Bose, Susmita (CRC Press, 2016)
Conceptually, 3D printing or layered manufacturing is a way to build parts without using any part-specific tooling or dies from the computer aided design (CAD) file of the part. Today most engineered devices are 3D printed first to check for their shape, size, and functionality before large-scale production. This book covers 3D printing technologies to their applications in different industries. The book is divided into two main parts-3D printing technologies and application of 3D printing technologies.
Keywords: Three-dimensional printing.; elektronické knihy; electronic books